The experience of nursing students facing death and dying - Viana Sampaio, Aline; Comassetto, Isabel; Mancussi e Faro, Ana Cristina; Dos Santos, Regina Maria; Silva Monteiro, Fernanda (Investigación y Educación en Enfermería, 2015)
Objective. To understand the phenomenon experienced by nursing students in their academic practices in view of death and dying. Method. This was a qualitative study, based on Martin Heidegger’s existential phenomenology, undertaken at a public University in Alagoas, Brazil, between August and October 2013. Seven senior students of nursing were interviewed. Results. The phenomenological analysis yielded the following existential themes: Facing death and dying in academic practice; Acknowledging impotence in the face of death; Glimpsing the possibility of solicitude; Interacting with the family in view of the loss; Experiencing spirituality in the face of dying. Conclusion. It is deduced that, during the academic education, the theme involving death and dying has been addressed insufficiently, without precisely attending to all the demands of the nursing students during care in the dying process. How to cite this article: Sampaio AV, Comassetto I, Faro ACME, Santos RM, Monteiro FS. The experience of nursing students facing death and dying. Invest Educ Enferm. 2015; 33(2):